In vivo applications of micro/nanorobots - Oral, Cagatay M; Pumera, Martin (Nanoscale, 2023)
Untethered robots in the size range of micro/nano-scale offer unprecedented access to hard-to-reach areas of the body. In these challenging environments, autonomous task completion capabilities of micro/nanorobots have been the subject of research in recent years. However, most of the studies have presented preliminary in vitro results that can significantly differ under in vivo settings. Here, we focus on the studies conducted with animal models to reveal the current status of micro/nanorobotic applications in real-world conditions. By a categorization based on target locations, we highlight the main strategies employed in organs and other body parts. We also discuss key challenges that require interest before the successful translation of micro/nanorobots to the clinic.
Keywords: robotika; Nanotechnology; Animals; nanotechnologie; zvířata; Robotics